Endoscopic suturing for the prevention of stent migration in benign upper gastrointestinal conditions: a comparative multicenter study - Ngamruengphong, Saowanee; Sharaiha, Reem Z.; Sethi, Amrita; Siddiqui, Ali A.; DiMaio, Christopher J.; Gonzalez, Susana; Im, Jennifer; Rogart, Jason N.; Jagroop, Sophia; Widmer, Jessica; Hasan, Raza Abbas; Laique, Sobia; Gonda, Tamas; Poneros, John; Desai, Amit; Tyberg, Amy; Kumbhari, Vivek; El Zein, Mohamad; Abdelgelil, Ahmed; Besharati, Sepideh; Hernaez, Ruben; Okolo, Patrick I.; Singh, Vikesh; Kalloo, Anthony N.; Kahaleh, Michel; Khashab, Mouen A. (Endoscopy, 2016)
Background and study aims: Fully covered self-expandable metal stents (FCSEMSs) have increasingly been used in benign upper gastrointestinal (UGI) conditions; however, stent migration remains a major limitation. Endoscopic suture fixation (ESF) may prevent stent migration. The aims of this study were to compare the frequency of stent migration in patients who received endoscopic suturing for stent fixation (ESF group) compared with those who did not (NSF group) and to assess the impact of ESF on clinical outcome. Patients and methods: This was a retrospective study of patients who underwent FCSEMS placement for benign UGI diseases. Patients were divided into either the NSF or ESF group. Outcome variables, including stent migration, clinical success (resolution of underlying pathology), and adverse events, were compared. Results: A total of 125 patients (44 in ESF group, 81 in NSF group; 56 benign strictures, 69 leaks/fistulas/perforations) underwent 224 stenting procedures. Stent migration was significantly more common in the NSF group (33 % vs. 16 %; P = 0.03). Time to stent migration was longer in the ESF group (P = 0.02). ESF appeared to protect against stent migration in patients with a history of stent migration (adjusted odds ratio [OR] 0.09; P = 0.002). ESF was also significantly associated with a higher rate of clinical success (60 % vs. 38 %; P = 0.03). Rates of adverse events were similar between the two groups. Conclusions: Endoscopic suturing for stent fixation is safe and associated with a decreased migration rate, particularly in patients with a prior history of stent migration. It may also improve clinical response, likely because of the reduction in stent migration.